Morphological Diversities revealed in Rahimi’s Novel The Patience Stone - Ariwibowo, Syamsuri (Faculty of Letters, Dr. Soetomo University, 2018)
This study aims to find out the diversity of morphemes appearing in every word in the novel. The problems being solved are the derivational morphemes expressed in the novel and the frequency of derivational morphemes that appear in The Patience Stone by Atiq Rahimi. Hopefully, it could be helpful and useful for application of derivational morpheme correctly. It can also be the reference for learning the word formation. The research method used to analyze the data is descriptive design. Data are taken from the novel of The Patience Stone about any words containing derivational morpheme and the technique of data analysis used is classification of every word and tabels of the frequency of derivational morpheme. The finding indicates that derivational suffix -ly is the most frequent morpheme that appears in the novel. The derivational suffix -hood and -ship are the least frequency of derivational morpheme. Key Words : Word-formation, Morpheme, Affixes